Production and purification of nipah virus glycoprotein in Spodoptera frugiperda 9 (J.E. Smith) insect cell - Sunhare, Raksha (2013)
Nipah virus glycoprotein (NiVG) expressed in Spodoptera frugiperda 9 [Sf9 (J.E.Smith)] induces neutralizing antibodies and could be used as an early detection reagent against NiV infection to prevent. Several industrial problems during the development of recombinant truncated glycoprotein of NiV (tNiVG) of baculovirus expression vector system (BEVs) from Sf9 insect cells were investigated in this study that included production, cell disruption techniques and purification. The production of recombinant tNiVG was enhanced by investigating the preferred medium and fermentation conditions of Sf9 cells. The maximum production of tNiVG was achieved by infecting Sf900 III serum free medium (SFM) developed middle exponential 5.0×106 cells/mL with quaternary amplified recombinant baculovirus at a multiplicity of infection (MOI) of 5. At the preferred condition, about 1.43 mg of tNiVG per 5.0×106 cells was obtained after 3 days of post–infection. The amount of tNiVG produced was equivalent to 40% of total cellular protein and thus maximum production was achieved from the insect cell–baculovirus expression vector system. Subsequent replacement of fresh Sf900 III SFM (every 3 days) reduced the doubling time (22 h) and achieved the maximum density (15.7×106 cells/mL) of Sf9 cells after 4 days. Hence, fresh Sf900 III SFM was used to study the effect of amplification of recombinant baculovirus, MOI and time of infection (TOI) on tNiVG production. The chemical lysis, freeze–thawing, high–pressure homogenisation and ultrasonication cell disruption methods were investigated to release the recombinant tNiVG from Sf9 cells. Among the investigated methods, high–pressure homogenisation with a single–pass successfully released 1.64 mg/mL tNiVG per 5.0×106 insect cells with a purity of 45% at high sample volume. Comparative evaluations of three immobilised affinity chromatography methods HisTrapTM FF 1 mL prepacked column, Ni SepFastTM MAG 1 mL adsorbent and conventional method for the recovery of tNiVG from Sf9 cells homogenate were investigated. The adsorption efficiency of applied clarified and unclarified feedstock onto HisTrapTM FF 1 mL prepacked column and Ni SepFastTM 1 mL MAG adsorbent was performed at 20 sodium phosphate mM, 500 mM sodium chloride, 20 mM imidazole and 5% glycerol containing pH 8 buffer. A single–step elution of bound tNiVG was performed with 20 mM sodium phosphate containing 250 mM sodium chloride, pH 7 buffer in the presence of 200 and 300 mM imidazole from HisTrapTM prepacked column and SepFastTM MAG adsorbent, respectively. Both IMAC operations achieved 94% purity and 92% recovery yield of tNiVG. Additionally, the unclarified feedstock application onto IMAC shortened the total processing time by about 13–fold as compared to the conventional method. Followed by a single–step purification strategy, SepFastTM Supor Q column of strong anion–exchange chromatography (AEC) was used to purify tNiVG produced in Sf9 insect cells. The preferred conditions of buffer to bind and to elute tNiVG were 50 mM sodium carbonate, pH 9 and 50 mM sodium citrate, pH 5. The use of elution buffer without sodium chloride separated the loosely bound tNiVG from the tightly bound major host proteins and subsequently avoided the desalting step as one of the further downstream processes. The developed method has recovered 89% tNiVG from the original supernatant with a protein purity of 90%. SDS–PAGE, Western blot and ELISA conformed purity and immunogenicity of single–step salt–free tNiVG (57 kDa). Further, the results of mass spectrometry confirmed the identity of tNiVG. Information obtained from these studies was useful for development of efficient production and single–step purification of recombinant tNiVG from Sf9 cells. The overall recovery yield and purity throughout the studies proposed unit operations assimple, economic and fast method for the development of tNiVG. Along with these,the single–step purified tNiVG could be used as a potential agent for the development of an immunoassay for NiV antibodies.